Ornamental aesthetics : the poetry of attending in Thoreau, Dickinson, and Whitman - Davis, Theo (Oxford University Press, 2016)
Theo Davis argues that ornamental aesthetics are central to Thoreau, Dickinson, and Whitman's writing, exploring the stakes of such an ornamental aesthetics through a parallel investigation of the ornamental aspects of Heidegger's phenomenological philosophy.